A comparison of a fluorescent antibody technique with a cultural method in the detection of infections with Shigella sonnei. Issue 3 (May 1964) - Taylor, C. E. D.; Heimer, G. V.; Lea, D. J.; Tomlinson, A. J. H.
Abstract : A comparison has been made of a fluorescent antibody technique with a cultural method for the detection of Sh. sonnei in faeces. The two methods were in agreement in 73% of the 394 specimens examined; 57 (14.5%) speciments were positive by culture only; 52 (13.2%) specimens gave positive results by fluorescence microscopy which were not confirmed by culture. Most of the latter are thought to be `false positive' results. The value and usefulness of fluorescence microscopy in the diagnosis of Sonne dysentery is discussed.